STUDENTS’ PERCEPTION OF USING THE MANGO LANGUAGES APPLICATION IN PRACTICING CONVERSATIONS TO IMPROVE SPEAKING SKILLS - Muhammad Ismail; Deasy Yunita Siregar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
English speaking skill is an essential competency in the 21st century, yet many Indonesian students face challenges such as limited practice, low confidence, and lack of opportunities in class. This study explored students’ perceptions of using the Mango Languages application to practice conversations and enhance speaking skills. Using a qualitative phenomenological approach, data were collected from 15 English education students through questionnaires and semi-structured interviews. Thematic analysis revealed five themes: enhanced confidence, vocabulary and pronunciation development, flexibility and accessibility, motivation and engagement, and challenges and limitations. Based on these identified themes, Mango Languages showed potential in reducing students’ anxiety, improving pronunciation accuracy, and supporting independent learning. However, challenges such as limited conversation topics, lack of direct teacher feedback, and technical barriers were also reported. Therefore, Mango Languages was best positioned as a supplementary tool for improving speaking skills in higher education when integrated with classroom instruction.